The Relativity of Day and Night in The Qur'an as the Needs of Living Creatures - Damayanti, Citra; Fitri Pangestuti, Desti; Hanifah, Hanny; Salsabila, Nurjihan; Najihah, Bannan Naelin (Journal of Ulumul Qur'an and Tafsir Studies, 2022)
This article discusses the alternation of day and night which is directly tied to the needs of living things, particularly humans. The phenomenon of day and night as well as it’s impact on the path of life organism, have been examined by Science and the Qur’an. The occurrence of day and night is the impact of the earth's motion (rotation and revolution). Humans, as living beings who acquired this highly organized gift, take advantage of day and night as the passage of time that impact their actions, emphasizing the significance of further research into the topic. This study employs a qualitative method in conjunction with library research strategy. This article finds that there is a link between alternation of day and night with time, environmental conditions, and how the body works in organism. From the standpoint of Science and Qur’an, the article is intended to in crease and understand information about the alternation of day and night (cosmography and geophysics).